Are Quebecers More Stressed Out at Work than Others? An Investigation into the Differences between Quebec and the Rest of Canada in the Level of Work Stress - Sedigh, Golnaz; Devlin, Rose Anne; Grenier, Gilles (Université d'Ottawa | University of Ottawa, 2016)
Stress at work is costly to individuals as well as employers, causing productivity to suffer and worker compensation claims to increase. Irrespective of how the data are grouped, individuals in Quebec are much more likely to report high work stress relative to those in any other Canadian province. Here we explore why this might be the case. Using pooled cross-sectional data from eight cycles of the Canadian Community Health Survey, spanning 2003-2012, we show that several factors are related to work stress, including chronic diseases, mental health, and lifestyle choices like smoking and drinking. Nevertheless, living in Quebec is persistently associated with higher reported work stress. We discuss whether contextual factors, like Quebec’s child-care policy and its legal regime may help us understand this result better; a ‘cultural’ explanation is explored, as is the possibility that Quebecers simply report more stress. While residents of Quebec do not appear to differ from others with respect to the prevalence of some ‘stress-related’ health conditions – pointing to a cultural component to the explanation – they are absent from work more often than others, suggesting that the costs to Quebec of this phenomenon are real.
Keywords: work stress; Canadian Community Health Survey; interprovincial comparisons of stress; Quebec; Canada; 1614E